Homicide in the Indian hills - Neubauer, Erica Ruth, 1979- (Neubauer, Erica Ruth, 1979- Jane Wunderly mysteries, 2025)
"Ooty, 1927: Accompanying Mr. Redvers on an assignment to Ootacamund to quell revolutionary rumblings, Jane finds there's more than meets the eye to India's Queen of Hill Stations. Ooty's lush tea plantations and tranquil gardens barely conceal its secrets--scandalous affairs, political sabotage, and a mounting anti-colonial movement. Even Redvers intends to subvert his official mission in Ooty by arranging a series of clandestine meetings with local resistance leaders. But it's not until the shocking death of a British national that Jane and Redvers are truly drawn into Ooty's deepest shadows. Jane's suspicions that the death is more than a tragic accident are soon confirmed, but word of a murder could stoke Ooty's simmering tensions into a full boil. Navigating corrupt local officials, festering personal vendettas, and a complicated network of bureaucratic entanglements that lead to the top tiers of government, Jane and Redvers edge closer to the truth . . . and its deadly consequences. Someone is willing to spill blood to protect their interests: will Jane become just another of Ooty's darkest secrets?"--Amazon.